Pengaruh tingkat kekayaan dan tingkat ketergantungan daerah terhadap kinerja pemerintah daerah - Primadiva, Parassela Pangestu; Rosdini, Dini; Mulyani, Sri (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2021)
This research discusses level of wealth and level of central dependence on local governments in West Java Province within the fiscal year of 2018 and 2019. Performance was measured using the Sustainable Development Goals indicator. The population of the research was all local governments in West Java Province. The sampling technique used was saturated sampling method or census. The sample in this research were 27 district/city governments in West Java Province. Based on the results of SPSS statistical analysis with multiple linear regression, it can be concluded that the level of local wealth and the level of central dependence have a significant effect on the performance of local governments. Â